Patient Safety Climate in Danish Primary Care: Adaption and Validation of the Danish Safety Attitudes Questionnaire (SAQ-DK-PRIM) [Response to Letter] - Juhl MH; Olesen AE; Deilkås ET; Bruun NH; Obling KH; Rytter N; Larsen MD; Kristensen S (Clinical Epidemiology)
Marie Haase Juhl,1,2 Anne Estrup Olesen,1,2 Ellen Tveter Deilkås,3 Niels Henrik Bruun,4 Kirsten Høgh Obling,5 Nikoline Rytter,6 Maya Damgaard Larsen,6 Solvejg Kristensen7 1Department of Clinical Pharmacology, Aalborg University Hospital, Aalborg, Denmark; 2Department of Clinical Medicine, Aalborg University, Aalborg, Denmark; 3Health Services Research Unit, Akershus University Hospital, Lørenskog, Norway; 4Research Data and Biostatistics, Aalborg University Hospital, Aalborg, Denmark; 5Care and Rehabilitation, Department of Health and Care Services (Danish: “Pleje og Rehabilitering, Staben Sundhed og Omsorg”), the Municipality of Aarhus, Aarhus, Denmark; 6Digitalization and Quality, Department of Health and Care Services (Danish: ‘Digitalisering og Kvalitet, Sundhed og Omsorg’), the Municipality of Aarhus, Aarhus, Denmark; 7Aalborg University Hospital, Psychiatry, Aalborg, Denmark